New data on the genus Tamolia Horváth, 1900 (Hemiptera: Heteroptera: Tessaratomidae), with description of a new species - Carvajal, Mariom A.; Faundez, Eduardo I.; Rider, David A. (Zootaxa, 2015)
The first specific locality data within New Guinea is provided for Tamolia ramifera (Walker, 1868). The male genitalia of this species is described for the first time. Tamolia ancalagon n. sp. is described from Karimui, New Guinea.